A Study of Significant Factors Affecting Viscoelastic Damping Properties of Polymer Materials - Vasina, Martin; Poschl, Marek; Zadrapa, Petr (Manufacturing Technology Journal, 2018)
Viscoelastic behaviour of materials is connected with transformation of mechanical energy into heat, which is a measure of a material structural damping. Viscoelastic properties of materials are described by different quantities, e.g. by loss modulus, storage modulus and loss factor. They depend on material type, its structure, excitation frequency, temperature, relative humidity etc. Damping properties were experimentally measured by means of the forced oscillation method. The purpose of the paper was to investigate viscoelastic damping properties of different polymer materials like PE, PP, ABS or rubber. There were studied different factors that have an influence on viscoelastic damping properties of the investigated polymer materials under dynamic loading, mainly the effect of operating temperature, excitation frequency, sample deformation and rubber composition.
Keywords: Viscoelastic Damping; Loss Factor; Excitation Frequency; Deformation; Temperature